Ways for Recycling of Quartz Waste in the Production of Silicate Materials - Pavlova, Irina; Zemlyanoi, Kirill; Farafontova, Elena; Girenko, Galina (KnE Materials Science, 2020)
The technological properties of quartz waste associated with the clay deposit are investigated by way of emission spectral analysis, petrography and X-ray phase analysis. This study considers the possibility of quartz waste utilization in the production of dry building mixtures as a filler, magnesia-quartz proppants as a raw material component, cement as a siliceous component, fine ceramics as a partially fluxing and exhausting component, silicate brick as the main raw material. In the production of glass and glassware it is possible to make use of the quartz waste as a glass-forming component including silicate blocks after refining for the Al2O3 and Fe2O3 content. Quartz waste can be recommended as molding sand after refining for the contents of Fe2O3, Na2O, K2O, MgO, CaO. Improvement of the properties of the quartz waste can be achieved by ways of elutriation to remove the clay component as well as magnetic separation to remove magnetic compounds of iron. Keywords: quartz waste, proppants, glass, cement, silicate brick, building mixtures, fine ceramics, molding sand, recycling